Multi-scale investigation of the performance of limestone in concrete. (30th January 2015) - Bentz, Dale P.; Ardani, Ahmad; Barrett, Tim; Jones, Scott Z.; Lootens, Didier; Peltz, Max A.; Sato, Taijiro; Stutzman, Paul E.; Tanesi, Jussara; Weiss, W. Jason
Highlights: The acceleration ability of fine limestone in cements depends on the polymorph. Calcite provides favorable surfaces for nucleation and growth, aragonite does not. Thermally converting the aragonite to calcite restores its acceleration ability. The acceleration ability of limestone produces stronger limestone-based concretes. Abstract: Limestone (calcium carbonate, CaCO3 ) has long been a critical component of concrete, whether as the primary raw material for cement production, a fine powder added to the binder component, or a source of fine and/or coarse aggregate. This paper focuses on the latter two of these examples, providing a multi-scale investigation of the influences of both fine limestone powder and conventional limestone aggregates on concrete performance. Fine limestone powder in the form of calcite provides a favorable surface for the nucleation and growth of calcium silicate hydrate gel at early ages, accelerating and amplifying silicate hydration, and a source of carbonate ions to participate in reactions with the aluminate phases present in the cement (and fly ash). Conversely, the aragonite polymorph of CaCO3 exhibits a different crystal (and surface) structure and therefore neither accelerates nor amplifies silicate hydration at a similar particle size/surface area. However, because these two forms of CaCO3 have similar solubilities in water, the aragonite does contribute to an enhancement in the reactivity of the aluminate phases in the investigated systems, chiefly via carboaluminate formation. In 100% ordinary Portland cement (OPC) concretes, 10% of the OPC by volume can be replaced with an equivalent volume of limestone powder, while maintaining acceptable performance. A comparison between limestone and siliceous aggregates indicates that the former often provide higher measured compressive strengths at equivalent levels of hydration, even when the two aggregate types exhibit similar elastic moduli. This suggests that the interfacial transition zone in the limestone-based concretes exhibits a higher degree of bonding, likely due to the favorable physical (texture) and chemical nature of the limestone surfaces. These observations reinforce the value of utilizing limestone to increase the performance and sustainability of 21st century concrete construction.